Numerische Simulation wirbeldynamischen Instabilitätsverhaltens turbulenter Vormischflammen - Voigt, Torsten (KIT Scientific Publishing, 2015)
This work contributes to an improved understanding of the driving mechanisms of the upstream propagation of turbulent premixed flames in enclosed vortex tubes within stationary gas turbine combustion systems. For this purpose, a Flamelet approach based on coupling a transport equation of the flame surface density with the description of laminar Flamelets to turbulent conditions is developed. This coupled approach enables the deduction of an explanation of this flashback phenomenon.